Obesity and risk for respiratory diseases: a Mendelian randomization study - Yang, Wenwen; Yang, Yanjiang; Guo, Yan; Guo, Jinde; Ma, Minjie; Han, Biao (Frontiers in Endocrinology, 2023)
Background: No existing comprehensive Mendelian randomization studies have focused on how obesity affects respiratory diseases.Methods: BMI and waist circumference, mainly from the UK Biobank, and 35 respiratory diseases from the FinnGen Biobank were subjected to Mendelian randomization analyses. In this study, the inverse variance weighting method was used as the predominant analysis method and was complemented by MR-Egger and weighted median methods. Horizontal pleiotropy and potential outliers were detected by employing the MR-PRESSO method.Results: This study indicated that obesity rises the possibility of acute upper respiratory infections (BMI: OR=1.